Republic of Madagascar : Fourth Review Under the Poverty Reduction and Growth Facility and Requests for Extension of the Arrangement and Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report, 2004)
Madagascar showed strong economic growth and low inflation under the Poverty Reduction and Growth Facility (PRGF) Arrangement. Executive Directors commended these developments, and stressed the need to restore fiscal discipline, improve governance, strengthen the business climate to encourage private investment, and accelerate structural reforms. They welcomed the plan to privatize and rehabilitate the telecom, cotton, sugar, and utility companies, and agreed that Madagascar has successfully completed the fourth review under the PRGF program, and approved waiver, additional interim assistance, and an extension of the arrangement.